Los recursos audiovisuales y su incidencia en el proceso de enseñanza y aprendizaje de la asignatura de Ciencias Naturales de los estudiantes del sexto grado de EB de la Escuela “Alonso de Mercadillo”, sección matutina, de la ciudad de Loja, periodo 2019- 2020. Lineamientos alternativos - Sanchez Maza, Katherine Cecibel (2020)
Research on audiovisual resources and their impact on the teaching and learning process of the Natural Sciences course of sixth grade EB students from the “Alonso de Mercadillo” School, morning section, in the city of Loja, period 2019- 2020. Alternative guidelines have the general objective of determining the incidence of audiovisual resources in the teaching and learning process of Natural Sciences in sixth grade students of Basic Education of the aforementioned institution. The type of study is descriptive and its qualitative-quantitative design; the applied methods were: observational, descriptive, inductive, deductive, hermeneutic, scientific, analytical, synthetic and statistical; the techniques: interview and survey; the instruments: questionnaire; and, the procedures: diagnosis, theoretical foundation and the design of alternative guidelines; Hence, in this last procedure, the diagnosis made in the teaching and learning process of Natural Sciences was taken as a reference, in which the detected problem is the monotonous- traditional application of certain audiovisual resources, which are the product of ignorance of other types of active procedures aimed at the training of students. The participating population was 88 students and four teachers from the sixth grades of Basic General Education. The work is concluded confirming that the different audiovisual resources, such as: Videos, multimedia, posters, among others; they contribute significantly to the teaching and learning process of the subject; since teachers and students can use benefits such as motivation and interest.